Recombinant Human Erythropoietin Protects Myocardial Cells from Apoptosis via the Janus-Activated Kinase 2/Signal Transducer and Activator of Transcription 5 Pathway in Rats with Epilepsy - Bao-Xin Ma, MD; Jie Li, MD; Hua Li, MD; Sui-Sheng Wu, MD (Elsevier, 2015)
Objective: To investigate the potential mechanisms underlying the protective effects of recombinant human erythropoietin (rhEPO) and carbamylated EPO (CEPO) against myocardial cell apoptosis in epilepsy. Methods: Rats were given an intra-amygdala injection of kainic acid to induce epilepsy. Groups of rats were treated with rhEPO or CEPO before induction of epilepsy, whereas additional rats were given a caudal vein injection of AG490, a selective inhibitor of Janus kinase 2 (JAK2). At different time points after seizure onset, electroencephalogram changes were recorded, and myocardium samples were taken for the detection of myocardial cell apoptosis and expression of JAK2, signal transducer and activator of transcription 5 (STAT5), caspase-3, and bcl-xl mRNAs and proteins. Results: Induction of epilepsy significantly enhanced myocardial cell apoptosis and upregulated the expression of caspase-3 and bcl-xl proteins and JAK2 and STAT5a at both the mRNA and protein levels. Pretreatment with either rhEPO or CEPO reduced the number of apoptotic cells, upregulated bcl-xl expression, and downregulated caspase-3 expression in the myocardium of epileptic rats. Both myocardial JAK2 and STAT5a mRNAs, as well as phosphorylated species of JAK2 and STAT5a, were upregulated in epileptic rats in response to rhEPO-but not to CEPO-pretreatment. AG490 treatment increased apoptosis, upregulated caspase-3 protein expression, and downregulated bcl-xl protein expression in the myocardium of epileptic rats. Conclusions: These results indicate that myocardial cell apoptosis may contribute to myocardial injury in epilepsy. EPO protects myocardial cells from apoptosis via the JAK2/STAT5 pathway in rats with experimental epilepsy, whereas CEPO exerts antiapoptotic activity perhaps via a pathway independent of JAK2/STAT5 signaling.